DETERMINAN PERTUMBUHAN LABA PADA CONSUMER GOODS INDUSTRY SUB SECTOR FOOD AND BEVERAGES DI MASA PANDEMI - Izzah Kholilah; Ana Kadarningsih (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to examine the effect of current ratio, net profit margin, and return on assets on company performance as seen from the Profit Growth of the consumer goods industry sub-sector food and beverages listed on the Indonesia Stock Exchange during the year 2016-2020. The population used in this study were 32 companies. The sampling technique used purposive sampling method with certain criteria and obtained 25 samples of companies. The analytical methods used in this research are multiple linear regression analysis, multiple correlation analysis, classical assumption test, model feasibility test, and hypothesis testing using SPSS version 25 program. The results showed that the current ratio had no significant effect on profit growth, net profit margin had a significant negative effect on profit growth, while return on assets had a significant positive effect on profit growth.